Treatment of Venous Thromboembolism in Patients with Congenital Deficiency of Antithrombin III - Schulman, S; Tengborn, L (Thrombosis and Haemostasis, 1992)
The treatment course of all thromboembolic events in the patients with congenital deficiency of antithrombin III (AT III) in the national Swedish register was reviewed in order to assess the appropriate medical therapy in this situation. The medical treatment of 70 events of venous thromboembolism was evaluated. There were eight cases with signs of clinical progression. The risk of therapeutic failure with heparin could be as low as 1.5% or as high as 9.2%. It would not be cost-effective to substitute with concentrates of AT III in every case with congenital deficiency thereof in connection with acute venous thromboembolism. “Heparin resistance” does not seem to be a problem in the vast majority of these patients.